Case report: A new de novo 6q21q22.1 interstitial deletion case in a girl with cerebellar vermis hypoplasia and developmental delay and literature review - Minotti, Chiara; Graziani, Ludovico; Sallicandro, Ester; Digilio, Maria Cristina; Falasca, Roberto; Alesi, Viola; Novelli, Giuseppe; Dentici, Maria Lisa; Loddo, Sara; Novelli, Antonio (Frontiers in Genetics, 2024)
Interstitial deletions involving 6q chromosomal region are rare. Less than 30 patients have been described to date, and fewer have been characterized by high-resolution techniques, such as chromosomal microarray.Deletions involving 6q21q22.1 region are associated with an extremely wide and heterogeneous clinical spectrum, thus genotype-phenotype correlation based on the size of the rearranged region and on the involved genes is complex, even among individuals with overlapping deletions.Here we describe the phenotypic and molecular characterization of a new 6q interstitial deletion in a girl with developmental delay, intellectual disability, cerebellar vermis hypoplasia, facial peculiar characteristics, ataxia and ocular abnormalities. Microarray analysis of the proposita revealed a 7.9 Mb interstitial de novo deletion at 6q21q22.1 chromosomal region, which spanned from nucleotides 108,337,770 to 116,279,453 (GRCh38/hg38).The present case, alongside with a systematic review of the literature, provides further evidence that could aid to the definition of the Smallest Region of Overlap and of the genomic traits that are associated with particular phenotypes, focusing on neurological findings and especially on cerebellar anomalies.